The death of detainees in police custody in Kuala Lumpur from year 2003 until year 2008: were they the victims of force? / Zulaikha Fardi … [et al.] - Fardi, Zulaikha; Laurentius, Timothy; Arifin, Muhammad Akram; Md Zain, Ahmad Afiq (2009)
This project in its present form is the result of the death of the detainees in police custody. The initial idea was to determine the existence of forces in some of the case which contributes to the death of the detainees in police custody. Some cases, the death of the detainees in police custody seems to be suspicious and causes the media and the public to make their own assumptions and speculations on the matter. Some of the forces are necessary made to the detainees in order to look for information in the process of the interrogation. There could be a direct force and indirect force. However the issue here is whether the force inflicted exceed what necessary, whether the power to use force is abused and whether the force legal or illegal. The existence of the usage of force that might contribute to the death of the detainees would be determined from the analysis of the statistics, interviews and reports made. The contributions of this project are twofold. First is to find solutions to the increasing number of the death of detainees in police custody. Secondly would be to increase the public awareness to their duties and rights in regard to this issue.